Nucleotide sequences of glycoprotein I and E genes of equine herpesvirus type 4 - Damiani, A.M. (Tokyo Univ. (Japan). Faculty of Agriculture); Matsumura, T; Yokoyama, N; Maeda, K; Miyazawa, T; Kai, C; Mikami, T (Journal of Veterinary Medical Science, 1998)
The nucleotide sequences of the glycoprotein I (gI) and E (gE) genes of equine herpesvirus type 4 (EHV-4) strain TH20 were determined. The predicted region encoding the EHV-4 gI gene is 1,263 nucleotides, corresponding to a polypeptide of 420 amino acids in length. The predicted region encoding the EHV-4 gE gene is 1,647 nucleotides, corresponding to a polypeptide of 548 amino aids in length. The EHV-4 gI and gE genes show 74% and 86% identity at the amino acid level with those of equine herpesvirus type 1 (EHV-1), respectively. Furthermore, we have found an open reading frame homologous to the EHV-1 gene 75, which overlaps in part with the 3' end of EHV-4 gE gene. These sequence data will be useful for development of a modified live vaccine against equine herpesvirus type 1 and 4 infections